Optimizing of microalgae scenedesmus sp. Biomass production in wet market wastewater using response surface methodology - Mohd Apandi, Najeeha; Muhamad, Mimi Suliza; Radin Mohamed, Radin Maya Saphira; Mohamed Sunar, Norshuhaila; Al-Gheethi, Adel; Gani, Paran; A. Rahman, Fahmi (MDPI, 2021)
The present study aimed to optimize the production of Scenedesmus sp. biomass during the phycoremediation process. The biomass productivity was optimized using face centred central composite design (FCCCD) in response surface methodology (RSM) as a function of two independent variables that included wet market wastewater concentrations (A) with a range of 10% to 75% and aeration rate (B) with a range of 0.02 to 4.0 L/min. The results revealed that the highest biomass productivity (73 mg/L/d) and maximum growth rate (1.19 day